The Cold Never Bothered Us Anyway - de César Netto, César (Journal of the Foot & Ankle, 2023)
Dear colleagues, Writing this editorial article for the Journal of Foot & Ankle is a great pleasure and honor. It is also fantastic to watch the growth of the Journal and its strength, influence, and respect among the International Orthopedic Foot and Ankle Community. I'm a girl's dad, and after watching Disney's Frozen movie at least a million times in the last several years, I cannot avoid making a parallel of us, Latin Americans Foot and Ankle Surgeons, and the main Frozen's character, Princess Elsa. Elsa was blessed with mighty powers that she could not understand or control initially, which kept her sad and isolated. However, she was unstoppable once she could dedicate time and effort to understanding her capabilities and started funneling her powers to achieve specific goals. I was always very proud of my roots and origins. Still, I remember being extremely concerned regarding how I would be able to transition and blend into the North American and International Orthopedic Foot and ankle Community. I worried about not fitting in or being diminished. I quickly found out that the recognition and respect we have rightfully conquered throughout the years, thanks to the hard and excellent work performed by several of our Latin American Foot and Ankle icons and ancestors, had paved the way for any Latin American surgeon to blossom and succeed anywhere in the globe they decided to go. A solid and indexed journal is crucial for us to fit and participate and also highlight and unleash the top-notch quality of our surgeons and researchers. The importance of our commitment to our journal is paramount at this point. The strength of a journal comes from its authors and articles. It is beautiful to see so many researchers with different levels of experience from all over Latin America participate and collaborate in publishing their high-quality articles and supporting our journal to grow strong. Returning to Disney Frozen and Princess Elsa and the iconic “Let it Go” song that echoed inside many brains for a long time, I would now recommend that we go the other route. Let’s not let it go. Do not let it go. Let’s go all in. Everything that we do daily in our practices could be something interesting to be turned into a research project and a manuscript eventually. Things we all do could be teaching and guiding surgeons anywhere and everywhere in Latin America and worldwide. Small changes in planning and organization, setting up a team, and a strategy can support any and all of us to contribute to becoming researchers and strengthen our academic and scientific production. It is a lot of fun. So that “Brostrom” that you do every week in your own way with excellent results could influence other surgeons and other patients. The only thing you need is to put the information out. We need to organize, understand, and control our power and funnel it to strengthen our research and our journal. Don’t let it go and start/keep doing it!